Strategi Personal Branding melalui Instagram dalam Pembentukan Citra Diri Mahasiswa Generasi Z di Kota Medan: Perspektif Komunikasi Digital - Muhammad Rasyad Ghazali Saraan; Ramdeswati Pohan (Mahesa Research Center, 2026)
and self-image in digital spaces. Instagram has become a prominent platform utilized by Generation Z students to strategically build personal branding. This study aims to analyze the process of personal branding through Instagram in shaping the self-image of Generation Z students in Medan City from a digital communication perspective. The research employs a qualitative approach with a case study design and a constructivist paradigm. Informants were purposively selected, consisting of active students who consciously use Instagram for personal branding. Data were collected through in-depth interviews, digital observation, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that personal branding is constructed through impression management, content selection, message consistency, authenticity, and active audience engagement. Instagram functions as a space for digital identity formation, contributing to academic reputation enhancement, social capital expansion, and professional opportunities. The study highlights that successful personal branding depends on balancing authenticity with the demands of social media presence. The contribution of this research lies in strengthening a digital communication-based personal branding model within the context of university students.